A 32 Factorial Design Approach for Formulation and Optimization of Azilsartan Medoxomil Nanosuspension for Solubility Enhancement - Shirsath, Nitin; Marathe, Dipak; Jaiswal, Priyanka; Zawar, Laxmikant (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Azilsartan medoxomil (AZL) is an orally active nonpeptide angiotensin II receptor antagonist with less water solubility and oral bioavailability. Objectives: Increase the solubility and dissolving rate of AZL. Materials and Methods: For formulation we used a probe sonication approach to create nanocrystals. The impacts of independent factors such as % polymer concentration (X1) and sonication duration (X2 min) on dependent variables such as particle size (Y1 nm) and % drug release (DR) were optimised using a 32 response surface methodology (Y2). Results: The prepared batches were examined for size, polydispersity index (PDI), zeta potential, solubility study and dissolution study. AZL nanocrystal (PS2 batch) particle size and zeta potential was found to be 168 ± 10 nm, 0.314 ± 0.02 and - 22.72 ± 2.6 mV respectively. The batch (PS2) with the best results was chosen and subjected to additional testing. In vitro dissolution of all 13 batches and pure drug was in ranges of 51.98-81.99% and 11.23 %, respectively. Conclusion: The FTIR analysis indicated that AZL and soluplus have no physical interaction. DSC, XRD, and SEM investigations revealed that the crystalline form of the medication was converted to an amorphous form, resulting in an improve water solubility and dissolution rate. Thus the studies exhibited nanocrystals prepared by probe sonication method showed significant enhancement in solubility and dissolution rate.
Keywords: Azilsartan medoxomil (AZL); Nanocrystal; Sonication; Solubility; Drug release